2018
DOI: 10.1242/dmm.032383
|View full text |Cite
|
Sign up to set email alerts
|

A novel zebrafish intestinal tumor model reveals a role for cyp7a1-dependent tumor-liver crosstalk in tumor's adverse effects on host

Abstract: The nature of host organs and genes that underlie tumor-induced physiological disruption on the host remains ill-defined. Here, we establish a novel zebrafish intestinal tumor model that is suitable for addressing this issue, and find that hepatic cyp7a1, the rate-limiting factor for synthesizing bile acids [or, in the case of zebrafish, bile alcohol (BA)], is such a host gene. Inducing krasG12D by Gal4 specifically expressed in the posterior intestine resulted in the formation of an intestinal tumor. The loca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…To some extent, LZTFL1 roles in mammalian was partially addressed, but limited data are available about the LZTFL1 function in zebrafish. The zebrafish is a powerful model organism for the study of vertebrate biology, being well suited to both developmental and human disease such as obesity, diabetes, and cancer (Elbialy et al, 2018; Enya et al, 2018; Gehrig et al, 2018; Gore et al, 2018). In the current study, the full-length cDNA of LZTFL1 was identified, which was 897-bp-long with a prediction of 299 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, LZTFL1 roles in mammalian was partially addressed, but limited data are available about the LZTFL1 function in zebrafish. The zebrafish is a powerful model organism for the study of vertebrate biology, being well suited to both developmental and human disease such as obesity, diabetes, and cancer (Elbialy et al, 2018; Enya et al, 2018; Gehrig et al, 2018; Gore et al, 2018). In the current study, the full-length cDNA of LZTFL1 was identified, which was 897-bp-long with a prediction of 299 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…In a highly original paper by Kawaoka and colleagues, the authors developed a model for Kras-driven intestinal cancer and studied the systemic effects of the tumour on otherwise healthy tissues. They discovered that, despite the benign state of the tumour, it induced systemic phenotypes that included liver inflammation, hepatomegaly and overall growth delay (Enya et al, 2018). The mechanism for the liver inflammation was found to be mediated via the host cyp7a1 gene that regulates hepatic cholesterol–BA metabolism.…”
Section: Cancer Models In Zebrafishmentioning
confidence: 99%
“… 19. For whole larval bile salt measurement, because the larval body weight is difficult to measure and there is no correlation between the larval body length and total bile salt levels [43], the total bile salt amount of each animal is plotted directly without normalization. For adult liver bile salt measurement, the total bile salt amount is normalized to the liver weight.…”
Section: Notesmentioning
confidence: 99%